Normal Total Leukocyte Count in Patients Despite Acute Appendicitis Clinically and Preoperatively - Ali Raza, Hazrat Bilal, Hadees, Muhammad Haris, Abdul Qudoos, Ghulam Shabbir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The main objective of this study was to ascertain the proportion of individuals diagnosed with acute appendicitis who exhibited clinically and preoperatively normal levels of total leukocyte count. Methodology: During the months of June 2021 and March 2022, researchers from the Department of Surgery at Jinnah Postgraduate Medical Center in Karachi, Pakistan, conducted a prospective observational study. All the patients presented with an impression of acute appendicitis above the age of twelve were included. Complete history, clinical examination, emergency investigations including CBC, UCEs, Ultrasound, X-Rays, Alvarado score were recorded in a predefined pro forma. Patients with low ALVARADO score and normal TLC with signs and symptoms of acute appendicitis were compared with CRP levels which directed the decision of appendectomy rather than conservative management. Per operative findings of stages of acute appendicitis such as acute inflamed, suppurative, gangrenous and perforated appendix were also noted. Appendix was sent to the laboratory and histopathological reports of the specimen were assessed. Results: Patients diagnosed with acute appendicitis and subsequently operated on totaled 270 in the study, 156 (57.78%) were having and ALVARADO score of less than 7 mostly due to normal TLC, while 114 patients (42.22%) were having ≥ 7 ALVARADO score. Preoperatively and histopathological reports of 270 patients of appendicitis 25% patents were acutely inflamed/catarrhal stage , 15.5% gangrenous, 20.59% perforated, while higher number of patients i.e. 38.91 were suppurative appendicitis. Conclusion: Most patients presenting with symptoms of acute appendicitis have normal TLC, meaning low TLC. This needs to be confirmed by caring out by proper examinations and getting inflammatory markers or in cases confirmatory CT if diagnosis can not be made clinically or by lab investigations. Keywords: Appendicitis, ALVARADO score, C-reactive protein, total leukocyte count